2017
DOI: 10.3389/fcimb.2017.00153
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Probiotics on Constipation in Children: A Systematic Review and Meta-Analysis of Six Randomized Controlled Trials

Abstract: Context: Constipation in children is a prevalent, burdensome, and psychologically important pediatric issue, the treatment of which remains a global challenge. The use of probiotics has been reported for management of the gastrointestinal microbiota.Objective: This study reviewed the existing literatures of 6 Randomized Control Trials (RCTs) to ascertain some baseline understanding and available information for the effects of probiotics on stool frequency and consistency in children with constipation.Data Sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
2
44
0
1
Order By: Relevance
“…Based on this finding, some studies have used active probiotics to treat anxiety disorders. Probiotics, defined as living microorganisms, are believed to provide health benefits [14,15]. Probiotics refer to ingested microorganisms with benefits for both humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this finding, some studies have used active probiotics to treat anxiety disorders. Probiotics, defined as living microorganisms, are believed to provide health benefits [14,15]. Probiotics refer to ingested microorganisms with benefits for both humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, there are several mechanisms that can potentially explain the action of probiotics in the treatment of functional constipation: modification of the gut microbiota, considering the changes that have been shown in individuals with constipation; increased production of lactate and short chain fatty acids, reducing luminal pH, which could improve colonic peristalsis and decrease intestinal transit time. 8,[29][30][31] Taking this into consideration, there is a growing interest in using probiotics in the treatment of constipation.…”
Section: The Use Of Probiotics For the Treatment Of Constipation In Cmentioning
confidence: 99%
“…In the literature, five systematic review articles were found, 30,[33][34][35][36] Two had a meta-analysis, 30,34 which addressed the use of probiotics in the treatment of functional constipation in children and adolescents. An article published in 2010 33 included two clinical trials in children 18,21 and three adult trials, and concluded that only L. rhamnosus Lcr35 showed a beneficial effect for the treatment of constipation in children.…”
Section: Lactobacillus Casei Rhamnosus Lcr35mentioning
confidence: 99%
See 2 more Smart Citations